2005
DOI: 10.1590/s0101-81752005000300045
|View full text |Cite
|
Sign up to set email alerts
|

Biologia da traça das crucíferas, Plutella xylostella Linnaeus (Lepidoptera, Yponomeutidae), sob condições controladas de temperatura, e parasitóides associados: Part III. Estudo sobre a biologia de Apanteles piceotrichosus (Blanchard) (Hymenoptera, Braconidae): análise do efeito de endocruzamento

Abstract: O endocruzamento em populações naturais resulta em uma perda na variabilidade genética que pode influenciar, a mortalidade juvenil e adulta, o tamanho, a viabilidade e fertilidade da prole, bem como a morfologia dos indivíduos. Apanteles piceotrichosus (Blanchard, 1943) (Hymenoptera, Braconidae) é um parasitóide de Plutella xylostella Linnaeus,1758 (Lepidoptera, Yponomeutidae) que tem atraído muita atenção com o propósito de biocontrole, pois pode ser utilizado como agente de controle biológico. Para a criação… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…However, many studies have failed to detect inbreeding depression on adult life span ( Johnson and Hutchinson 1993;De Clercq et al 1998;Nieminen et al 2001;Markert et al 2004;Prezotti et al 2004;Radwan et al 2004;Goncalves and Di Mare 2005) and others have shown that the effect of inbreeding on adult life span varies among lines or populations (Fowler and Whitlock 1999;Swindell and Bouzat 2006) and among rearing conditions (Pray et al 1994). Unfortunately, most detailed studies of the genetics of life span and mortality rates, and the effects of inbreeding on life span and mortality rates, use Drosophila as a model system (Clarke and Maynard Smith 1955;Hughes 1995;Pletcher et al 2000;Hughes et al 2002;Vermeulen and Bijlsma 2004;Swindell and Bouzat 2006).…”
mentioning
confidence: 99%
“…However, many studies have failed to detect inbreeding depression on adult life span ( Johnson and Hutchinson 1993;De Clercq et al 1998;Nieminen et al 2001;Markert et al 2004;Prezotti et al 2004;Radwan et al 2004;Goncalves and Di Mare 2005) and others have shown that the effect of inbreeding on adult life span varies among lines or populations (Fowler and Whitlock 1999;Swindell and Bouzat 2006) and among rearing conditions (Pray et al 1994). Unfortunately, most detailed studies of the genetics of life span and mortality rates, and the effects of inbreeding on life span and mortality rates, use Drosophila as a model system (Clarke and Maynard Smith 1955;Hughes 1995;Pletcher et al 2000;Hughes et al 2002;Vermeulen and Bijlsma 2004;Swindell and Bouzat 2006).…”
mentioning
confidence: 99%